(untitled) (Bangladesh Journal of Medical Science, 2025)
Periodontal disorders (PD), also known as gum disease, involve inflammation and infection of the gum and bone tissue, which are preventable and treatable. Many worldwide suffer from such conditions, particularly in low- and middle-income countries. Risk factors related to periodontitis include poor oral cleanliness, regular alcohol consumption, betel quid chewing, and intake of tobacco. PD also raises the risk of fatal systemic diseases by provoking systemic inflammation. Oral homeostasis and prevention of periodontitis require healthy microbiota. PD results from alteration of the oral and gut microbiome environment. This host-microbe equilibrium interruption leads to inflammation, and tissue breakdown further acts to nourish the pathogens. There are several surgical and non-surgical means for managing PD. However, the positive impact of probiotics, which include the genera Lactobacillus and Bifidobacterium, on PD has been noted. Probiotics kindle the immune system and synthesize antiinflammatory cytokines that activate T regulatory cells. They also build antimicrobial molecules and inhibit oral pathogens. This narrative review was done to note the effects of probiotics on PD. The research used electronic search engines, including PubMed, Scopus, and Google Scholar. This study indicates that probiotics may be used as adjuvant therapy for gum disease. This may aid in faster healing, and since probiotics are found in accessible food sources like yogurt, the wider population may benefit. Thus, the global population may enjoy excellent oral health and an improved quality of life. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 331-361